Optimization Design of the New Knotting Device and Its Parametric Driving - Wu Naiqing; Han Yapeng; Cui Shihai; Ma Xishan (Jixie chuandong)
Considering the efficiency and environmental issue in balloon inflating and sealing up work,an innovate design scheme cooperated by a variety of transmission structure which is ingenuity and meets the green design concept is put forward. Taking the core component cylindrical cam as an example and the parametric design analysis in its process is expounded and the mechanism is controlled to achieve precise movement by using function expression. On this basis,the optimization design based on the parameter- driven is further studied,by using the genetic algorithm in Matlab optimization toolbox and taking the resistance moment of inverse cam mechanism as objective,the model is modified and the parameter is reset by using the optimization result. The verification is carried out through the functional prototype testing and motion simulation analysis in Recur Dyn solver in UG software,and the optimized design in all the parameter driving is perfected.